Internship at Worten Digitópia - Chaves, José Diogo Madureira (2021)
This internship report for my master’s degree in Sound and Image at Universidade Católica Portuguesa is presented as a curricular internship report and describes all work developed at Worten Digitópia, who has provided me with the opportunity to learn and work in the area of electronic sound production at Casa da Música. The work portrayed in this report comprehend different projects ranging from pre-production and production for live orchestral concerts to sampling and programming for audio. This internship also allowed me to apply and explore skills I acquired during my years as a student at the School of Arts of Universidade Católica Portuguesa, as well as giving me the opportunity to explore other areas and acquiring new skills, to shape my vision as a professional and as an artist.